PERENCANAAN APLIKASI RCM DENGAN ANALISA KUALITATIF PADA STASIUN PENGOLAHAN BIJI SAWIT - Legisnal Hakim; Fahrizal - (Universitas Pasir Pengaraian, 2011)
In this globalization, companies are have to increase productivity in order to produce maximum output. In this case, especially system productivity company. Smoothness system or production process is supported by many aspects, one of which is the aspect of reliability of existing machinery or equipment in the production system.In palm oil mills, there are two processing stations and processing of palm fruit processing palm kernel. Palm kernel oil processing systems, among others, Pressing, Nut fiber, Depricarper, Polishing drum, cyclone Nut, Nut hoper, Ripple mill, LTDS 1 & 2, Claybath. To increase the productivity of these systems need to be an appropriate activity treatment on the machine or equipment, in an effort to increase conduction reliability of the equipment in the system kernel oil processing. For it is necessary for treatment planning method RCM (Reliability Centered Maintenance) using qualitative analysis where the RCM method can determine the identification of critical equipment and components, optimum care, treatment and consequences of activity intervals failures in machinery or equipment or core processing system palm on palm oil mills company.